2020
DOI: 10.1016/j.atherosclerosis.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The proteoglycan mimecan is associated with carotid plaque vulnerability and increased risk of future cardiovascular death

Abstract: Background and aims: A vulnerable plaque is an atherosclerotic plaque that is rupture-prone with a higher risk to cause cardiovascular symptoms such as myocardial infarction or stroke. Mimecan or osteoglycin is a small leucine-rich proteoglycan, important for collagen fibrillogenesis, that has been implicated in atherosclerotic disease, yet the role of mimecan in human atherosclerotic disease remains unknown. Methods: 196 human atherosclerotic carotid plaques were immunostained for mimecan. Smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Therefore, our results suggest that the increased serum OGN levels observed in T2D patients with mildly impaired kidney function (eGFR < 90 mL/min/1.73 m 2 ) are mainly related with renal rather than vascular damage. Endorsing our findings, a recent study observed increased immunostaining of OGN in human atherosclerotic carotid plaques from patients with lower eGFR values [44]. However, further studies are needed to clarify the relationship between OGN and CVD.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, our results suggest that the increased serum OGN levels observed in T2D patients with mildly impaired kidney function (eGFR < 90 mL/min/1.73 m 2 ) are mainly related with renal rather than vascular damage. Endorsing our findings, a recent study observed increased immunostaining of OGN in human atherosclerotic carotid plaques from patients with lower eGFR values [44]. However, further studies are needed to clarify the relationship between OGN and CVD.…”
Section: Discussionsupporting
confidence: 85%
“…Mimecan is a keratan sulphate proteoglycan that has been described as an emerging biomarker of atherosclerosis [103]. In human carotid plaques, its presence was recently shown to be downregulated in vascular smooth muscle cells but upregulated in certain plaque regions (close to collagen fibres and neutral lipids) [104]. The same study also showed a positive correlation between plaque levels of mimecan and age, with higher levels predicting future cardiovascular-related death.…”
Section: Resultsmentioning
confidence: 96%
“…Originally isolated from bovine bone [ 62 ], mimecan/osteoglycin (OGN) is a small leucine-rich proteoglycan, fundamental in collagen fibrillogenesis and in cellular growth, differentiation, and migration control [ 63 ]. Its aberrant expression was described as occurring in several human and other mammal disorders, from cardiovascular risk [ 64 ] to hypothalamic–pituitary–adrenal (HPA) axis dysfunctions [ 65 ], from obesity and related co-morbidities [ 66 , 67 ] to tumorigenesis [ 68 ], cancer [ 69 , 70 , 71 ], and bone homeostasis defects [ 72 ].…”
Section: Resultsmentioning
confidence: 99%